Sistem Informasi Monitoring Kepadatan Pengunjung dan Pembelian Tiket Wisata Berbasis Web pada Dinas Pariwisata Kota Padang - Muhammad Zikri (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2026)
Padang City has significant tourism potential, with a variety of natural, cultural, historical, and culinary destinations that attract tourists. However, information on visitor density levels and ticket purchasing services are still not integrated, making it difficult for tourists to obtain the latest information and book tickets efficiently. This research aims to design and build a Web-Based Visitor Density Monitoring and Ticket Purchase Information System to support the provision of real-time information and improve the effectiveness of tourism destination management in Padang City. The system was developed by integrating features for visitor density monitoring, online ticket purchasing, payment verification, data management for destinations, staff, and facilities, as well as the presentation of analytical reports. Based on the results of analysis, design, implementation, and testing, the system is able to integrate the monitoring and ticket transaction processes into a single platform, facilitating computerized data management. Real-time visitor density information helps tourists determine more convenient visit times, while the online ticket purchasing feature enhances transaction convenience. Furthermore, the resulting analytical reports support the Padang City Tourism Office in more effective monitoring, evaluation, and decision-making..